Rapid switching capability and efficient magnetoelectric coupling mediated by effective interfacial interactions in Bi0·9La0·1FeO3/SrCoO3 bi-phase composites for ultra-sensitive pulsating devices - Umer Waqas; Muhammad Umar Salman; Muhammad Ahmed Khan; Shahid M. Ramay; Farooq Ahmad; Saira Riaz; Shahid Atiq (Journal of Materials Research and Technology, 2024)
Magnetoelectric coupling and switching charge density in multiferroics have gained the attention of researchers around the world for energy storage, energy harvesting, and their potential applications for pulsating devices. In multiferroics, the absence of inversion symmetry and the presence of antiferromagnetic symmetry give rise to intriguing magnetoelectric coupling. In this paper, bi-phase composites, (1–x)Bi0·9La0·1FeO3 + xSrCoO3 for x = 0.1, 0.2, 0.3 are made by a facile and time-saving sol–gel auto-combustion technique. For this, we employed lanthanum-doped BiFeO3 to avoid the volatilization of bismuth ions. The composition 0.8Bi0·9La0·1FeO3 + 0.2SrCoO3 (x = 0.2) showed the maximum polarization (Pmax = 2.45 × 10−3 μC/cm2) and effective interfacial interactions depicting symmetrical magnetoelectric coupling response with least distortion along with significant switching charge density (i.e., Qsw = – 2.124 × 10−5 μC/cm2). Whereas reduction in leakage current density is observed with the inclusion of SrCoO3 contents into pure BLFO during polarization phenomena, confirming its insulating properties. Switching charge density from the positive-up- negative-down sequence not only ensured the suitability of switching applications in pulsating devices but also displayed its reliability and long-term stability. The symmetric magnetoelectric coupling showed its potential use in piezoelectric actuators and energy harvester applications. Magnetic attributes and multidomain structures were confirmed by the vibrating sample magnetometer. The maximum value of the squareness ratio appears to be 0.1035 confirming the existence of a multidomain structure for all samples. These outcomes suggest that this particular composition seems extremely viable in developing ultra-sensitive pulsating devices attributed with significant switching charge density.